The semantic web : 3rd Asian Semantic Web Conference, ASWC 2008 Bangkok, Thailand, December 2008 Proceedings - Asian Semantic Web Conference (3rd : 2008 : Bangkok, Thailand); Domingue, John; Chutiporn Anutariya (Berlin : Springer, 2008)
13